Outcome of off-pump coronary artery bypass graft (OPCAB) surgery: Analysis of 129 cases - Alam, AKM Manzurul; Ahmed, Istiaq; Ahmed, Manzil; Hossain, Al Mamun (Bangladesh Heart Journal, 2016)
Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide, including Bangladesh. Besides medical and interventional treatment, coronary artery bypass graft (CABG) surgery in an effective modality for the management of a subset of CAD patients. Off-pump coronary artery bypass graft (OPCAB) surgery is a recent modification of conventional CABG surgery, which, like other parts of the world, is being increasingly practiced in Bangladesh. But the outcome of this relatively recent surgical approach in our setting is largely unknown. In this study, the outcomes of 129 cases off-pump CABG surgery done in a tertiary cardiovascular centre and a private institute in Dhaka were analyzed. Majority (67, 54.2%) had triple vessel disease (TVD), while 4 (3.2%) patients had left main disease. One, two and three grafts were used in 17 (13.2%),74 (57.4%) and 38 (29.4%) cases respectively. There was no mortality. Post-operative complications occurred in 17 (13.18%) patients; secondary wound infection in 10 (7.75%) and immediate respiratory distress in 7 (5.43%) cases. Ten (7.75%) patients needed secondary stitches. Bangladesh Heart Journal 2016; 31(1) : 23-25